Physical Processing-Assisted pH Shifting for Food Protein Modification: A Comprehensive Review - Ruiqi Long; Yuanyuan Huang; Mokhtar Dabbour; Benjamin Kumah Mintah; Jiayin Pan; Minquan Wu; Shengqi Zhang; Zhou Qin; Ronghai He; Haile Ma (Foods, 2025)
The increasing demand for sustainable protein sources has intensified interest in improving the processing efficiency of traditional proteins and developing novel alternatives, particularly those derived from plants and algae. Among various processing technologies, pH shifting has attracted attention due to its simplicity, low cost, and capacity to effectively alter protein structure and functionality. However, employing pH shifting alone requires extremely acidic or alkaline conditions, which can lead to protein denaturation and the generation of undesirable by-products. To address these limitations, this review explores the integration of pH shifting with physical processing techniques such as ultrasound, high-pressure processing, pulsed electric fields, and thermal treatments. Moreover, this review highlights the effects of these combined treatments on protein conformational transitions and the resulting improvements in functional properties such as solubility, emulsification, foaming capacity, and thermal stability. Importantly, they reduce reliance on extreme chemical conditions, providing greater sustainability in industrial applications, particularly in food product development where milder processing conditions help preserve nutritional quality and functional properties. In that sense, this combined treatment approach provides a promising and eco-efficient protein modification strategy, and bridges technological innovation with sustainable resource utilization.